An estimation of groundwater type and origin of the complex karst catchment using hydrological and hydrogeochemical parameters : a case study of the Gacka river springs - Lukač Reberski, Jasmina; Kapelj, Sanja; Terzić, Josip (2009)
Summary: Karst aquifers are heterogeneous terrains, where it is hard to assess any hydraulic parameter. Therefore, a multidisciplinary approach is necessary for research on karst aquifers. Catchment area of the Gacka river springs is typical Dinaric karst terrain built of karstified carbonates. Groundwater flow is mostly directed by preferential flow paths usually connected with main faults and fracture zones. In the presented case study structural geological and tectonic characteristics were defined. A recession diagram was created, and the water balance was calculated. Tracer-test data were also used for analysis. All these data were compared with the bulk hydrogeochemical and isotopic analyses of spring and surface waters. For this purpose, samples were obtained every month for one hydrological year at 17 sampling locations. Processing of all these data allowed a tenable definition of the Gacka spring catchment area
Bibliografija: 36 jed
Keywords: Hidrogeologija -- Hidrogeokemija -- Krš; Gacka